2023
DOI: 10.1007/s11357-023-00843-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphic metabolic and cognitive responses of C57BL/6 mice to Fisetin or Dasatinib and quercetin cocktail oral treatment

Abstract: Senolytic treatment in aged mice clears senescent cell burden leading to functional improvements. However, less is known regarding the effects of these compounds when administered prior to significant senescent cell accumulation. From 4–13 months of age, C57BL/6 male and female mice received monthly oral dosing of either 100 mg/kg Fisetin or a 5 mg/kg Dasatinib (D) plus 50 mg/kg Quercetin (Q) cocktail. During treatment, several aspects of healthy aging were assayed including glucose metabolism using an insulin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
0
18
1
Order By: Relevance
“…We found differences in SAB positivity, expression of splicing factors and expression of mRNAs encoding SASP proteins between male and female cells in response to female sex hormones. Sex differences in drug responses are not uncommon, and a sexual dimorphism has been reported in mice in response to senotherapeutics [ 65 , 66 ]. Recently, the NIA Interventions Testing Program in mice has revealed sex differences in effects on longevity in response to 17-α-estradiol and aspirin [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found differences in SAB positivity, expression of splicing factors and expression of mRNAs encoding SASP proteins between male and female cells in response to female sex hormones. Sex differences in drug responses are not uncommon, and a sexual dimorphism has been reported in mice in response to senotherapeutics [ 65 , 66 ]. Recently, the NIA Interventions Testing Program in mice has revealed sex differences in effects on longevity in response to 17-α-estradiol and aspirin [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the link between cellular senescence and aging is indisputable [ 51 ], the differential analysis of these clocks limits our interpretation of their clinical significance. However, the advantages of senolytic treatments have shown greater nuances, as detrimental and sex-based effects have been seen in mice [ 52 ]. Indeed, previous literature has shown varied benefits among mice models and human trials with the application of senolytics [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, D+Q treatment has been shown to overcome negative effects of estrogen-deficiency, such as postmenopausal osteoporosis [41]. We previously discussed a possibility of D+Q treatment leading to low estrogen levels in normal aging C57BL/6 mice [20], however, data support the sometimes contradictory differential effects of early intervention between normal aging and mouse models of AD [31]. This, combined with the general lack of characterization of estrogen levels across disease progression in APP NL-F/NL-F mice, makes it difficult to determine if the effects of D+Q treatment in APP NL-F/NL-F mice are mediated through modulating estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…Senotherapeutic concentrations and dosing strategy were based on previous publications [20, 43, 45]. APP NL-F/NL-F mice were dosed with 100 mg/kg of Fisetin while a cocktail of 5 mg/kg of D + 50 mg/kg of Q, or vehicle (2% DMSO in canola oil) by oral administration [45].…”
Section: Methodsmentioning
confidence: 99%